PELAKSANAAN PENGAWASAN INSPEKTORAT PROVINSI LAMPUNG TERHADAP PENYUSUNAN DOKUMEN PELAKSANAAN ANGGARAN - Indah Maulidiyah MSK; Ahmad Hernawan (Legalita, 2021)
Making Terms of Reference and implementing the supervision of the Lampung Province Inspectorate on the preparation of Budget Implementation Documents that have not been optimal is an interesting thing to study, how is the implementation of the Terms of Reference (TOR) in the preparation of the Budget Implementation Documents by the Regional Apparatus of Lampung Province; as well as how the supervision of the Lampung Provincial Inspectorate of the Budget Implementation Documents Preparation by the Lampung Provincial Apparatus. The purpose of this research is to 1) knowing that there is a TOR will make it easier for the supervisory apparatus to supervise and measure the performance of the implementation of an activity; 2) knowing the implementation of supervision by the Inspectorate of Lampung Province on the preparation of Budget Implementation Documents by the Regional Apparatus of Lampung Province.